ANALISIS SEGMENTASI PASAR TERHADAP HARGA SEPEDA MOTOR AUTOMATIC YAMAHA MIO PADA PT . HASJRAT ABADI KOTAMOBAGU - PAPUTUNGAN, INDRIYATI; Tumbel, Tinneke M.; Tarore, Henny S. (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
By lookong at the development of a motorcycle thar is increasingly rapidly, manymanufacturers of the new motor started to go to indonesia. The large number of thenew motor started to go to indonesia. The large number of existing motorcyclecompany raises competitive. Pressure on industi motorcycle Consumer needs anddesires are very multiform against type or brand of motorcycles then request thecommunity againts motorcycles continue to experience increased, therefore, marketinkrekatif and put the market strategy, take advantage of opportunities that arise in themarket related to the desires of the commonity therefore companies should set theprice according to the quality of the product because the price setaffect the quantitysold is because the price of the very influential towards the success of the productsmarketed by the company. The aim in this study is whether there is a connectionbetween the market segmentation with the price of motorbikes and detect otherfactorsthat also affect the market share within the company bike motors. Thisresearch is quantitative reseacrch using a simple linear regression analysisapproach. Engineering data collection done by spreading the questionnaire filled by75 respondents and analyzed using simple regression analysis and use test resultsfrom t. Linear regression analysis is a simple variabel market segmentationneffect against prices. Hypothesis test andresults showedthat thevariables simultaneously influential market segmentation significantly to price. Based on the results of thisresearch, companies Yamaha Indonesia to make the latest innovations inaccordancewiththe community's lifestyle and always give you the design and the latest models inaccordance with advances automotive world.Keywords : Market segmentation, Pricing